Dispensing manufacturing process of automobile airtight plastic-coated copper bar

By optimizing the surface treatment of copper strips and introducing plasma cleaning, as well as precise control of vibration treatment and glue curing conditions, the problem of insufficient airtightness in traditional automotive airtight plastic copper strip manufacturing processes is solved, significantly improving the airtight performance and product stability.

CN119518384APending Publication Date: 2025-02-25GUANGDONG SHENGLAN NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411570608.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the traditional automotive air-tight plastic-encapsulated copper strip manufacturing process, insufficient air-tightness is prone to occur at the junction of copper strips and plastics, and the effect of the dispensing process is affected by a variety of factors, resulting in poor air-tightness performance.

Method used

The optimized copper strip surface treatment process, including electroplating, passivation treatment and ultrasonic cleaning, combines plasma cleaning steps to activate the copper strip and plastic surfaces, and ensure uniform coating and complete curing of the glue through vibration treatment and precise control of the glue curing conditions.

Benefits of technology

It significantly improves the adhesion between the glue and the substrate, avoids the generation of air holes, improves the airtight performance of the automotive airtight plastic copper strip, and ensures the safety and performance of the vehicle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518384A_ABST
    Figure CN119518384A_ABST
Patent Text Reader

Abstract

The invention relates to a dispensing manufacturing process of an automobile airtight plastic-coated copper bar, and aims to provide an efficient and reliable copper bar sealing method so as to improve the airtight performance of automobile parts. According to the process, firstly, a copper material is precisely machined into a copper bar with the required shape and size through a stamping process, and then the copper bar is subjected to electroplating and passivating treatment or cleaning treatment, so that the surface performance and cleanliness of the copper bar are enhanced. Thirdly, the treated copper bar is placed in an injection mold, the treated copper bar and a plastic material are subjected to integrated injection molding, and a preliminary composite structure is formed; and then, the plasma cleaning technology is used for cleaning the area needing glue dispensing, the copper bar and the plastic surface are activated, and the surface energy is detected to ensure that the subsequent glue dispensing requirement is met. Then, silica gel is dispensed on the activated surface through an automatic dispensing machine to serve as sealant, and gas in the pouring sealant is promoted to be exhausted through vibration treatment. And finally, the product is placed in an oven to be heated and cured, and a firm sealing layer is formed. According to the manufacturing process provided by the invention, the airtight performance of the automobile airtight plastic-coated copper bar can be remarkably improved, and the automobile airtight plastic-coated copper bar has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of automobile copper busbar manufacturing, and in particular to a glue-dispensing manufacturing process for automobile airtight plastic-coated copper busbars. Background Art

[0002] In the automotive industry, airtightness is crucial to vehicle safety and performance. In electric and hybrid vehicles, in particular, battery packs, motors, and other electrical systems require high airtightness to prevent the ingress of moisture, dust, and other contaminants, ensuring stable operation and extending the system's service life. As a key component in these systems, the airtightness of automotive plastic-coated copper busbars directly impacts the performance and reliability of the entire vehicle.

[0003] The traditional manufacturing process for automotive airtight plastic-coated copper busbars often presents several challenges. First, the junction between the copper busbar and the plastic is prone to insufficient airtightness, primarily due to incomplete surface treatment or poor material bonding during the injection molding process. Second, the effectiveness of the glue dispensing process, a key means of improving airtightness, is often affected by a variety of factors, including glue application uniformity, adhesion between the glue and the substrate, and glue curing.

[0004] To improve the airtightness of automotive airtight plastic-coated copper busbars, the industry has made various attempts. For example, improving the copper busbar's surface treatment process to enhance the bonding strength between the busbar and the plastic; optimizing injection molding process parameters to improve the fusion between the plastic and the busbar; and selecting appropriate glue and dispensing techniques to improve glue coating uniformity and adhesion.

[0005] However, while these attempts have improved the airtightness of automotive airtight plastic-coated copper busbars to a certain extent, some problems still exist. For example, the surface energy of the copper busbar after surface treatment is insufficient, resulting in weak adhesion between the glue and the copper busbar; gas in the glue cannot be effectively discharged during the dispensing process, resulting in pores in the cured glue layer, affecting airtightness; and improper curing conditions lead to incomplete curing of the glue, thus affecting its sealing effect. Summary of the Invention

[0006] The present application provides a dispensing manufacturing process for automobile airtight plastic-coated copper busbars to solve the above-mentioned problems, improve the airtight performance of automobile airtight plastic-coated copper busbars, and ensure the safety and performance of vehicles.

[0007] In order to achieve the above objectives, this application provides the following technical solutions:

[0008] A glue-dispensing manufacturing process for an automotive airtight plastic-coated copper busbar comprises the following steps:

[0009] a) Copper busbar stamping: Select copper material and process it into copper busbars of required shape and size through stamping process;

[0010] b) Surface treatment of copper busbar: electroplating and passivation treatment of the copper busbar, or cleaning with weak acid or alkali solution, hydrocarbon solvent, or ultrasonic cleaning to clean the surface of the copper busbar;

[0011] c) Injection molding: Place the treated copper busbar in an injection mold and perform integral injection molding with the copper busbar to form a preliminary product;

[0012] d) Plasma cleaning: Place the preliminary product in a plasma cleaning device, or use a plasma gun to clean the area where glue is to be dispensed. The cleaning time range is 80 seconds to 200 seconds, and the cleaning power range is 200 watts to 400 watts. At the same time, helium is introduced with a flow rate range of 90 ml to 150 ml to activate the copper busbar and plastic surface. After cleaning, use a dyne pen to test the surface energy to ensure that the surface energy is greater than or equal to 32mN / m.

[0013] e) Dispensing: Use an automatic or manual dispensing machine to apply sealant on the activated surface;

[0014] f) Vibration treatment: Place the dispensed product on a vibration plate and vibrate it at a set frequency for 5 to 15 minutes to promote the discharge of gas in the potting compound;

[0015] g) Glue curing: The glue is cured by heating in an oven or letting it stand naturally. The oven heating time is 60 minutes and the baking temperature is 135 degrees.

[0016] In one embodiment, in the plasma cleaning step, the cleaning time is preferably 108 seconds, the cleaning power is preferably 300 watts, and the helium flow rate is preferably 110 ml.

[0017] In one embodiment, the sealant is silicone, epoxy or polyurethane.

[0018] The beneficial effects of this application are:

[0019] (1) By optimizing the copper busbar surface treatment process and introducing a plasma cleaning step, the present invention effectively cleans and activates the copper busbar and plastic surface, significantly improving the adhesion between the glue and the substrate. Furthermore, the addition of a vibration treatment step effectively promotes the discharge of gas from the potting compound, avoiding the formation of pores, thereby significantly improving the airtightness of the automotive airtight plastic-coated copper busbar.

[0020] (2) The plasma cleaning in this application not only cleans the surface, but also enhances the bonding strength between the copper busbar and the plastic through activation treatment, making the initial product after injection molding more solid and less prone to delamination or cracking.

[0021] (3) The present invention specifies the specific conditions for glue curing, including the oven heating time and temperature, or the natural standing time, to ensure that the glue can fully cure and achieve the best sealing effect. This not only improves the stability of the product, but also extends the service life of the product.

[0022] (4) By precisely controlling the time, power and helium flow of plasma cleaning, as well as the frequency and time of vibration treatment, the present invention optimizes process parameters, improves production efficiency and reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A flow chart of the dispensing manufacturing process for an automotive airtight plastic-coated copper busbar provided in one embodiment of the present application;

[0024] Description of reference numerals: DETAILED DESCRIPTION

[0025] The terms used in the implementation section of this application are only used to explain the specific embodiments of this application and are not intended to limit this application. The implementation of the embodiments of this application will be described in detail below with reference to the accompanying drawings.

[0026] The following will describe in detail the glue-dispensing manufacturing process for the automotive airtight plastic-coated copper busbar provided by the present invention in conjunction with specific embodiments.

[0027] Example 1

[0028] like Figure 1 As shown, a dispensing manufacturing process for an automotive airtight plastic-coated copper busbar specifically includes the following steps:

[0029] a) Copper busbar stamping:

[0030] Select the copper material that meets the requirements and process it into the copper busbar of the required shape and size through the stamping process. This step ensures that the copper busbar has a consistent size and shape, laying the foundation for subsequent processing.

[0031] b) Surface treatment of copper busbar:

[0032] The copper busbar is electroplated to enhance its surface hardness and corrosion resistance. After electroplating, it is passivated to further protect the copper busbar surface from oxidation. Alternatively, the copper busbar surface can be thoroughly cleaned with a weak acid or alkali solution, a hydrocarbon solvent, or ultrasonic cleaning to remove oil and impurities.

[0033] c) Injection molding:

[0034] The treated copper busbar is placed in an injection mold, ensuring accurate positioning. Plastic material is then injected and molded integrally with the copper busbar to form a preliminary product. During this step, the plastic material tightly wraps around the copper busbar, forming a preliminary composite structure.

[0035] d) Plasma cleaning:

[0036] Place the preliminary product in a plasma cleaning machine or use a plasma gun to clean the area where glue is to be dispensed. Set the cleaning time to 108 seconds, the cleaning power to 300 watts, and introduce helium at a flow rate of 110 ml. Plasma cleaning effectively activates the copper busbar and plastic surface, increasing the surface energy. After cleaning, use a dyne pen to test the surface energy to ensure it is greater than or equal to 32 mN / m to meet the requirements for subsequent glue dispensing.

[0037] e) Glue dispensing:

[0038] Use an automatic dispensing machine to apply silicone sealant to the activated surface. The automatic dispensing machine ensures uniform glue application and can precisely control the amount and location of glue applied.

[0039] f) Vibration treatment:

[0040] Place the dispensed product on a vibration plate and vibrate it at a set frequency for 10 minutes. This vibration treatment effectively promotes the expulsion of gas from the potting compound, preventing the formation of air holes in the cured adhesive layer, which could affect airtightness.

[0041] g) Glue curing:

[0042] Place the product in an oven and heat it for 60 minutes at a temperature of 135 degrees. Oven heating ensures that the glue is fully cured, forming a strong sealing layer, thereby improving the airtightness of the automotive airtight plastic-coated copper busbar.

[0043] Example 2

[0044] It is basically the same as Example 1, except that:

[0045] During the plasma cleaning step, the cleaning time was adjusted to 150 seconds, the cleaning power to 250 watts, and the helium flow rate to 130 ml. These parameter adjustments still ensured effective activation of the copper busbar and plastic surface, meeting the requirements of subsequent dispensing.

[0046] During the dispensing step, epoxy adhesive is selected as the sealant. Epoxy adhesive has good adhesion and corrosion resistance, which can further improve the airtightness and stability of the automotive airtight plastic-coated copper busbar.

[0047] Example 3

[0048] It is basically the same as Example 1, except that:

[0049] During the dispensing step, polyurethane is selected as the sealant. Polyurethane has excellent elasticity and wear resistance, making it suitable for applications that need to withstand certain mechanical stresses.

[0050] During the glue curing step, choose to let the glue cure naturally. The natural resting time depends on the ambient temperature and the type of glue. It usually takes a longer time, but it can avoid the thermal stress problems that may be caused by oven heating.

[0051] Comparative experiments and data analysis

[0052] In order to verify the effectiveness of the glue dispensing manufacturing process for automotive airtight plastic-coated copper busbars provided by the present invention, we conducted a comparative experiment and recorded the relevant data of the vibration verification after glue dispensing. The following is a detailed record of the experimental data:

[0053]

[0054] By analyzing the above data, we can draw the following conclusions:

[0055] The impact of plasma cleaning time: The data shows that plasma cleaning time has a certain impact on the airtightness test values. Within a certain range, the airtightness test values ​​tend to decrease with increasing cleaning time, but the relationship is not linear. This may be because proper plasma cleaning can more effectively activate the copper busbar and plastic surfaces, improving the adhesion of the glue to the substrate, thereby reducing the airtightness test values. However, excessive cleaning time may lead to over-activation of the surface, which in turn affects the adhesion of the glue.

[0056] The impact of adding hydrogen: Comparing the experimental data with and without hydrogen addition, we can find that the airtightness test values ​​are generally lower after adding hydrogen. This shows that the addition of hydrogen helps to further activate the surface, improve the adhesion of the glue, and thus improve the airtightness performance.

[0057] Impact of vibration time: Vibration time also has a certain impact on airtightness test values. The data shows that appropriate vibration time helps to promote the release of gas from the potting compound, reducing the airtightness test value. However, excessive vibration time may lead to uneven distribution of the glue, which in turn affects airtightness performance.

[0058] Impact of vibration pulse count: Similar to vibration duration, vibration pulse count also affects airtightness test values. Within a certain range, as the vibration pulse count increases, the airtightness test value tends to decrease. However, care should also be taken to avoid problems caused by excessive vibration.

[0059] In summary, comparative analysis of experimental data reveals that we can further optimize the dispensing manufacturing process parameters for the automotive airtight plastic-coated copper busbar of this invention to improve the product's airtightness and stability. For example, during the plasma cleaning step, appropriate cleaning time and power can be selected; after dispensing, appropriate vibration time and pulse count can be selected; and the addition of activating gases such as hydrogen can also be considered to further enhance airtightness.

[0060] In the description of the embodiments of this application, it should be noted that, unless otherwise expressly specified or limited, the terms "mounted," "connected," and "connected" should be understood in a broad sense. For example, they may refer to a fixed connection, an indirect connection via an intermediate medium, internal communication between two components, or an interaction between two components. Those skilled in the art will understand the specific meanings of the above terms in the embodiments of this application based on specific circumstances.

[0061] In the embodiments of the present application, any device or element referred to or implied must have a specific orientation, be constructed and operate in a specific orientation, and therefore should not be understood as limiting the embodiments of the present application. In the description of the embodiments of the present application, the meaning of "plurality" is two or more, unless otherwise specifically specified.

[0062] The terms "first", "second", "third", "fourth", etc. (if any) in the description and claims of the embodiments of the present application and the above-mentioned drawings are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that the numbers used in this way are interchangeable under appropriate circumstances, so that the embodiments of the present application described herein, for example, can be implemented in orders other than those illustrated or described herein. In addition, the terms "may include" and "have" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or apparatus that includes a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units that are not explicitly listed or inherent to these processes, methods, products or apparatus.

[0063] Finally, it should be noted that the above embodiments are intended only to illustrate the technical solutions of the embodiments of this application, and are not intended to limit them. Although the embodiments of this application have been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they may modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, such modifications or replacements do not deviate from the essence of the corresponding technical solutions within the scope of the various embodiments of this application.

Claims

1. A glue dispensing manufacturing process for automobile airtight plastic-coated copper busbar, characterized in that: The following steps are involved: a) Copper busbar stamping: Select copper material and process it into copper busbars of required shape and size through stamping process; b) Surface treatment of copper busbar: electroplating, passivation treatment, or cleaning with weak acid and alkali solution, hydrocarbon solvent, or ultrasonic cleaning to clean the surface of copper busbar; c) Injection molding: placing the treated copper busbar in an injection mold and molding it together with the copper busbar to form a preliminary product; d) Plasma cleaning: Place the preliminary product in a plasma cleaning device, or use a plasma gun to clean the area where glue is to be dispensed. The cleaning time ranges from 80 seconds to 200 seconds, and the cleaning power ranges from 200 watts to 400 watts. At the same time, helium is introduced with a flow rate range of 90 ml to 150 ml to activate the copper bus and plastic surface. After cleaning, use a dyne pen to detect the surface energy to ensure that the surface energy is greater than or equal to 32mN / m; e) Glue dispensing: Use an automatic or manual glue dispensing machine to apply sealant on the activated surface; f) Vibration treatment: Place the dispensed product on a vibration plate and vibrate it at a set frequency for 5 to 15 minutes to promote the discharge of gas in the potting glue; g) Glue curing: The glue is cured by heating in an oven or leaving it to stand naturally. The baking time for oven heating is 60 minutes and the baking temperature is 135 degrees.

2. The glue dispensing manufacturing process of the automobile airtight plastic-coated copper busbar according to claim 1 is characterized in that: In the plasma cleaning step, the cleaning time is preferably 108 seconds, the cleaning power is preferably 300 watts, and the helium flow rate is preferably 110 ml.

3. The glue dispensing manufacturing process for automobile airtight plastic-coated copper busbar according to claim 1 is characterized in that: The sealant is silicone, epoxy or polyurethane.